The Costs and Challenges of Implementing Trade Facilitation Measures - Moïsé, Evdokia (OECD Trade Policy Papers, 2013)
This study provides data on the costs and challenges of implementing trade facilitation measures currently under negotiation in the WTO. It updates an earlier study undertaken in 2005, presenting data and insights from nine additional developing countries. The study confirms earlier findings that the costs of putting in place and maintaining trade facilitation measures are not particularly large and are far smaller than the benefits gained from implementing these measures. Capital expenditure to introduce the measures ranged between EUR 3.5 and EUR 19 million, while annual operating costs did not exceed EUR 2.5 million. Information technologies and single window mechanisms seem the most expensive elements but the most important area is training, because of its role in changing business practices of border agencies. Some measures may be expensive to introduce but not costly to operate, others require political commitment rather than funds. Moreover, an increasing amount of technical and financial assistance to implement these measures has been made available to developing countries over the last decade